2017
DOI: 10.18632/oncotarget.18308
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs as potential biomarkers for coronary plaque rupture

Abstract: Coronary plaque rupture is the most common cause of acute coronary syndrome. However, the timely biomarker-based diagnosis of plaque rupture remains a major unmet clinical challenge. Balloon dilatation and stent implantation during percutaneous coronary intervention (PCI) could cause plaque injury and rupture. Here we aimed to assess the possibility of circulating microRNAs (miRNAs) as biomarkers of acute coronary plaque rupture by virtue of the natural model of PCI-induced plaque rupture. Stable coronary arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 42 publications
3
44
0
2
Order By: Relevance
“…The diagnostic value of miR-21 in the patient group in our study could be considered as moderate. From this point of view, our results are consistent with the literature [24] and the nomination of miR-21 for diagnosis can be con rmed by repeated studies.…”
Section: Discussionsupporting
confidence: 92%
“…The diagnostic value of miR-21 in the patient group in our study could be considered as moderate. From this point of view, our results are consistent with the literature [24] and the nomination of miR-21 for diagnosis can be con rmed by repeated studies.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, using DNA-gold nanoparticle probes, miRNA could be better applied in clinical praxis as biomarkers [7]. One research group showed that miR-155-5p, miR-483-5p, and miR-451a may support the early diagnostic value of coronary plaque rupture [8]. In addition to the reports described above, extensive research has indicated that miRNAs play important roles in KD development.…”
Section: Introductionmentioning
confidence: 99%
“…In order to identify the miRNAs relevant to a pathological condition, such II/R, it is important to find the miRNAs that are differentially expressed in biological samples taken from that condition. An effective method of such analysis is the microarrays assay, a high‐throughput screening method, has been widely used for investigating drug targets and mechanisms of diseases (Li et al ., ; Yuan et al ., ). Thus, the aim of the present work was to find the differentially expressed miRNAs associated with II/R injury by microarrays assay and then to investigate the molecular mechanisms and drug targets for the prevention and treatment of II/R injury.…”
Section: Introductionmentioning
confidence: 99%